Low grade fibromyxoid sarcoma (Evans tumour) of the arm - Shalaka Indap; Manjiri Dasgupta; Nilay Chakrabarti; Abhishek Agarwal (Indian Journal of Plastic Surgery)
A low-grade fibromyxoid sarcoma is a rare soft tissue tumour that has a tendency to develop in the deep soft tissue of young adults with potential for local recurrence or distant metastasis. We describe a 40-year-old female patient with a low-grade fibromyxoid sarcoma of the shoulder that had been excised twice in the past and then had recurred after a few months. A wide resection of this tumour with flap reconstruction was performed followed by radiation to the area. The patient had no evidence of local recurrence or distant metastasis at 2 years after surgery.